Semantic And Science Research Model: Relation Underground Water Concept With Agricultural Growth In Qur’an - Al Faruq, Abdul Qudus; Halimah, Ulfatul; Bakar, Abu (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
This research explores the relationship between the concept of underground water and agricultural plant growth as mentioned in the Qur'an, focusing on Surah Az-Zumar verse 21 and Al-Baqarah verse 74. The identified issue is the lack of research combining semantic and scientific approaches to understand this relationship, even though the concept was mentioned in the Qur'an long before modern scientific discoveries. The research study uses a descriptive-analytical method with a semantic and scientific approach, employing theories of isytiqaq (derivation) and siyaq (context) for Qur’anic text analysis. The research demonstrates that rainwater seeping into the ground and stored in underground reservoirs is a vital source of life, as illustrated in the Qur'an. The study argues that the Qur'an provides clear guidance on natural processes that sustain life, which is later validated by modern science, showcasing the scientific evidence of i'jaz ilmy in a broader context.